Spatiotemporal trends and drivers of global karst soil erosion based on trend and scenario indicators - Yan Yan; Mingxie Chen; Chuanyong Tang; Sheng Wang (PLoS ONE, 2026)
Karst ecosystems, 15% of Earth’s land, are critical for soil erosion research due to their unique geology and hydrology. This study investigated the patterns and trends of soil erosion in global karst regions from 2000 to 2020 using the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model combined with robust trend methods (Theil-Sen and Mann-Kendall). Correlation analysis and scenario analysis were employed to quantify the driving factors and evaluate the contributions of various factors. A global decline in erosion was found, with intense erosion in southwest Asia, southern Europe, and northwestern North America. Asia had the highest soil erosion rate, followed by North America, Europe, and other regions. Among them, the soil erosion rate in North America showed an upward trend. Russia, China, and Europe were key in erosion reduction (29.98%, 28.01%, 18.68%). Rainfall strongly correlated with erosion; vegetation’s link varied by region. Temperature negatively correlated with erosion in some areas. Scenario analysis quantified contributions of human activities (47.06%) and climate (26.68%). These findings highlight the joint role of natural and human factors in soil erosion management, important for crafting effective conservation strategies in karst areas globally.